Central sensitization in adults with chronic neck pain: cross-cross study exploring differences by gender - Ana Paula Vasconcellos Abdon; Leonardo Lima Aleixo; Amanda de Oliveira Toledo; Maíra de Oliveira Viana Rela; Carlos Ewerton Maia Rodrigues; Ticiana Mesquita de Oliveira Fontenele (BrJP, 2024)
BACKGROUND AND OBJECTIVES: The presence of central sensitization (CS) in people with chronic neck pain requires clarification, as does the possible disparities between genders. Therefore, this study aimed to evaluate the presence of CS in chronic neck pain according to gender. METHODS: Cross-sectional study with the participation of 260 adults (18-59 years old) with chronic neck pain, carried out between September 2022 and September 2023. Instruments were applied to collect sociodemographic profile, pain characteristics, cervical functional disability and presence of SC. The software SPSS 23.0 was used for comparative analyzes. RESULTS: Regarding disparities between genders, there were no differences in the intensity of pain and cervical functional disability (p=0.134 and p=0.277, respectively). However, SC was higher in women (43.5 ± 14.0; p=0.003). In females, CS was related to "pain interference" in the aspects of walking (r=0.311; p=0.001), relationships with people (r=0.309; p=0.001), appreciation of life (r=0.321; p= 0.001) and with cervical functional disability (r=0.570; p=0.001). In males, CS was related to "pain interference" in aspects such as general activity (r=0.311; p=0.008), mood (r=0.376; p=0.001), walking (r=0.313; p= 0.007), relationships with people (r=0.477; p=0.001), sleep (r=0.321; p=0.006), appreciation of life (r=0.427 p=0.001) and functional disability (r=0.667; p<0.001). CONCLUSION: Women with chronic neck pain showed a greater presence of CS, while CS in men was related to a variety of aspects that negatively affect life. Given this, differences between genders could be considered in the management of patients with chronic neck pain.